Obtenção de hidrogéis à base de amido e nanocelulose para potencial aplicação na agricultura - Hernandez, Cécile Chaves (Universidade Federal de São Carlos, 2025)
Hydrogels, due to their porous three-dimensional structure, have the ability to swell, absorbing fluids, a very important property when they are intended to be used in the field of agriculture as a superabsorbent polymer, helping to control soil moisture; as a soil conditioner, performing a controlled delivery of fertilizers and other agrochemicals or even for the removal of metal ions that accumulate in the soil due to its natural non-degradation. The present study proposes the preparation of a hydrogel obtained through a matrix of starch (cassava and arrowroot)/xanthan gum and starch (cassava and arrowroot)/xanthan gum with cellulose nanofibrils (CNFs) ionically, covalently and double crosslinked, forming a nanocomposite, to obtain better mechanical and physicochemical properties. The characterization techniques used in this study were: Differential Scanning Calorimetry (DSC), determination of Viscosity Average Molar Mass (Mv), Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), thermogravimetric analysis (TG), X-ray diffraction (XRD) and swelling analysis. It was observed that the different morphologies and amylose/amylopectin contents of the starches influence their viscosities, which directly interferes in the analyzed properties and that the presence of xanthan gum, and the crosslinks contribute to the formation of a dense and compact structure in the hydrogels. Double crosslinking produces an appearance of inflexibility and rigidity in the hydrogel. The density of the network formed after crosslinking and the presence of CNFs interfered in the thermal and swelling properties, causing a decrease in thermal stability and mass loss, with the main peak of mass loss between 153 °C and 167 °C, while for starch it occurs above 300 °C. After these analyses, it can be concluded that the presence of NFC in the hydrogels reduced the swelling power, since the interactions between NFC and starch reduce the mobility of the network. Good results were obtained for the different starch hydrogels and that covalent crosslinking confers greater swelling power to the material, with swelling power above 1000%. The results obtained for the covalently crosslinked samples being superior to those obtained by ionic crosslinking and doubly crosslinked.
Obtaining starch and nanocellulose-based hydrogels for potential application in agriculture
Keywords: Hidrogéis; Nanocelulose; Amido de araruta; Amido de mandioca; Amido de milho; hydrogels; nanocellulose; arrowroot starch; cassava starch; corn starch; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES